X-ray nanotomography and electron backscatter diffraction demonstrate the crystalline, heterogeneous and impermeable nature of conodont white matter. Issue 8 (4th August 2021) - Atakul-Özdemir, Ayse; Warren, Xander; Martin, Peter G.; Guizar-Sicairos, Manuel; Holler, Mirko; Marone, Federica; Martínez-Pérez, Carlos; Donoghue, Philip C. J.
Abstract : Conodont elements, microfossil remains of extinct primitive vertebrates, are commonly exploited as mineral archives of ocean chemistry, yielding fundamental insights into the palaeotemperature and chemical composition of past oceans. Geochemical assays have been traditionally focused on the so-called lamellar and white matter crown tissues; however, the porosity and crystallographic nature of the white matter and its inferred permeability are disputed, raising concerns over its suitability as a geochemical archive. Here, we constrain the characteristics of this tissue and address conflicting interpretations using ptychographic X-ray-computed tomography (PXCT), pore network analysis, synchrotron radiation X-ray tomographic microscopy (srXTM) and electron back-scatter diffraction (EBSD). PXCT and pore network analyses based on these data reveal that while white matter is extremely porous, the pores are unconnected, rendering this tissue closed to postmortem fluid percolation. EBSD analyses demonstrate that white matter is crystalline and comprised of a single crystal typically tens of micrometres in dimensions. Combined with evidence that conodont elements grow episodically, these data suggest that white matter, which comprises the denticles of conodont elements, grows syntactically, indicating that individual crystals are time heterogeneous. Together these data provide support for the interpretation of conodont white matter as a closed geochemical system and, therefore, its utility of the conodont fossil record as a historical archive of Palaeozoic and Early Mesozoic ocean chemistry.